2022
DOI: 10.3390/vaccines10111790
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Parents’ Willingness to Vaccinate Their Children against COVID-19 Infection and Their Perception of mRNA COVID-19 Vaccines

Abstract: Little was known about Malaysian parental attitudes, beliefs, and intentions surrounding coronavirus disease 2019 (COVID-19) vaccines for children when the National COVID-19 Immunization Program for Children (PICKids) was launched in February 2021. A cross-sectional online survey-based study was carried out from 15 March 2022 to 23 July 2022 on Malaysian parents/guardians of children between ages 5 and below 12 years old. A total of 15.7% reported being extremely willing, and 38.9% were somewhat willing to vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Participants most commonly mentioned the belief that the vaccine was an important preventive measure as the main reason for having received the vaccine whereas, unsurprisingly, concerns about the potential side effects and that it was not useful were identified as the leading reasons for a COVID-19 vaccine refusal. These results, which were in con-cordance with previous similar surveys conducted worldwide among different groups of individuals [14,25,33,37,38], underscore the need for intensified educational activities on the COVID-19 vaccine, which can address these incorrect beliefs. Moreover, it is important to note that a substantial minority (7.7%) reported that they had received the vaccine from the recommendation of a healthcare provider.…”
Section: Discussionsupporting
confidence: 86%
“…Participants most commonly mentioned the belief that the vaccine was an important preventive measure as the main reason for having received the vaccine whereas, unsurprisingly, concerns about the potential side effects and that it was not useful were identified as the leading reasons for a COVID-19 vaccine refusal. These results, which were in con-cordance with previous similar surveys conducted worldwide among different groups of individuals [14,25,33,37,38], underscore the need for intensified educational activities on the COVID-19 vaccine, which can address these incorrect beliefs. Moreover, it is important to note that a substantial minority (7.7%) reported that they had received the vaccine from the recommendation of a healthcare provider.…”
Section: Discussionsupporting
confidence: 86%
“…This study was consistent with (Wong et al, 2022) examination of the association between the function of health professionals and baby immunization coverage during the COVID-19 outbreak in children (Singh et al, 2020;Tanjung, 2020). The relationship between the role of health workers and complete basic immunization coverage during the COVID-19 pandemic in children, where health workers play a role in increasing community participation, particularly among mothers, but the success of the immunization program cannot be achieved without family support.…”
Section: Discussionsupporting
confidence: 85%
“…Parental vaccine hesitancy, may also be predicted by the vaccine type and origin ( 75 , 135 ). Parents may prefer conventional vaccines over mRNA vaccines due to lack of confidence in the mRNA technology and fear of its unknown side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Parents may prefer conventional vaccines over mRNA vaccines due to lack of confidence in the mRNA technology and fear of its unknown side effects. Another concern among parents is the possible existence of microchips in some COVID-19 vaccines ( 135 ). Some studies showed that the general population trust COVID-19 vaccines manufactured by their government ( 75 ) while others may trust vaccines produced by the international, well-known, and specialized drug and vaccine companies.…”
Section: Discussionmentioning
confidence: 99%